Verbal semantics and the left dorsolateral anterior temporal lobe: a longitudinal case of bilateral temporal degeneration. Issue 7 (2nd July 2020) - Vonk, Jet M. J.; Borghesani, Valentina; Battistella, Giovanni; Younes, Kyan; DeLeon, Jessica; Welch, Ariane; Hubbard, H. Isabel; Miller, Zachary A.; Miller, Bruce L.; Gorno-Tempini, Maria Luisa
ABSTRACT: Background: Semantic variant primary progressive aphasia (svPPA), a clinical syndrome characterized by loss of semantic knowledge, is associated with neurodegeneration that starts in the anterior temporal lobe (ATL) and gradually spreads towards posterior temporal and medial frontal areas. At the earliest stages, atrophy may be predominantly lateralized to either the left or right ATL, leading to different clinical profiles with the greatest impairment of word comprehension or visual/social semantics, respectively. Methods & Procedures: We report the in-depth longitudinal investigation of cognitive and neuroanatomical features of JB, an unusual case of ATL neurodegeneration with relative sparing of left lateral ATL regions. Outcomes & Results: Over the course of 9 years, neurodegeneration progressed to involve bilateral temporo-lateral and frontal regions, resulting in a relatively symmetric and diffuse frontotemporal atrophy pattern. In parallel, JB developed greater behavioral, cognitive, and language impairments, as well as signs of motor neuron disease at her last evaluation. Episodic memory and socio-emotional processing deficits arose, likely secondary to semantic verbal deficits, while visuospatial processing, executive function, and non-semantic language abilities remained largely unaffected throughout the course of the disease. Conclusions: The details of this rare case of early medial more than lateral ATL degeneration are consistent with a bilateral organization of the semantic system and, crucially, with a functional dissociation between medial paralimbic and lateral neocortical temporal regions. Cases of frontotemporal dementia (FTD) such as JB, who initially do not meet current clinical criteria for svPPA and instead present with some features of behavioral variant FTD, highlight the need for specific criteria for the right temporal variant of FTD that we propose could be called semantic variant FTD.